2021
DOI: 10.1016/j.resuscitation.2021.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in refractory out-of-hospital cardiac arrest before and after implementation of an ECPR protocol

Abstract: Aim: To compare the outcomes in patients with refractory out-of-hospital cardiac arrest (OHCA) fulfilling the criteria for extracorporeal cardiopulmonary resuscitation (ECPR) before and after implementation of an ECPR protocol, whether the patient received ECPR or not. Methods:We compared cardiac arrest registry data before (2014À2015) and after (2016À2019) implementation of the ECPR protocol. The ECPR criteria were presumed cardiac origin, witnessed arrest with ventricular fibrillation, bystander CPR, age 18À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
(16 reference statements)
2
8
0
1
Order By: Relevance
“…Further, almost all randomized patients in both prospective ECPR studies [ 7 , 8 ] had witnessed arrest with high rate of bystander CPR which is another important prerequisite for good outcomes. Moreover, only 6% of all OHCA patients were enrolled in the Prague OHCA trial which is in line with previous reports [ 21 , 22 ]. This confirms that ECPR is not a substitute for conventional ACLS but rather complementary method for properly selected refractory OHCA patients provided in the well-organized system [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 88%
“…Further, almost all randomized patients in both prospective ECPR studies [ 7 , 8 ] had witnessed arrest with high rate of bystander CPR which is another important prerequisite for good outcomes. Moreover, only 6% of all OHCA patients were enrolled in the Prague OHCA trial which is in line with previous reports [ 21 , 22 ]. This confirms that ECPR is not a substitute for conventional ACLS but rather complementary method for properly selected refractory OHCA patients provided in the well-organized system [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 88%
“…During the study period, randomized patients constituted 6% of all persons who experienced cardiac arrest and received CPR (Figure 1). This is comparable to the proportions in Vienna and other studies that have suggested 4% to 6% of OHCAs to be suitable for an intra-arrest transport approach . However, in these studies, potential candidates were evaluated retrospectively, whereas in this study, patients were evaluated during ongoing on-scene CPR.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the low number of potential eligible candidates (1.2%), compared to other studies. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated positive results of ECPR on neurologically intact survival, 4 , 5 , 6 but more recent registry studies could not demonstrate a beneficial effect on outcome. 7 , 8 Moreover, ECPR has a significant risk of complications (leg ischaemia, bleeding from the insertion site, infection and intracranial haemorrhage), and comes with significant cost and logistical challenges. Therefore, ECPR is only offered as a treatment to patients most likely to benefit and have a positive outcome.…”
Section: Introductionmentioning
confidence: 99%